Impact of Strategic Alliances on Competitive Advantage: A Field Study on Pharmaceutical Companies in the Republic of Yemen - Murad Mohammed Abdullah Al-Nashmi; Ali Salh Moqbel Al-Sakani (University of Science and Technology, Sana’a, Yemen, 2024)
This study aimed to determine the impact of strategic alliances on the competitive advantage of pharmaceutical companies in Yemen. The study followed a descriptive-analytical approach. The study population consisted of (9) pharmaceutical companies, with a total of (330) individuals, and due to the small size of the population, a complete census method was adopted. A questionnaire was used to collect data, which were statistically processed using the Statistical Package for the Social Sciences (SPSS). The results showed a high level of strategic alliance practices as well as a high level of competitive advantage achieved in the studied companies. The results also showed a statistically significant impact of strategic alliances in all their dimensions in achieving competitive advantage, with varying levels of this impact in achieving competitive advantage from one dimension to another. The results showed a positive direct impact of the dimensions (strategic alliance management, competitive cooperation, and technological alliances), while the results showed no impact for both (shared vision and marketing alliances). Additionally, the results revealed a negative (inverse) impact of the dimension (sharing resources, risks, and costs) in achieving the competitive advantage of the studied companies. The study recommends the formation of strategic alliances among the studied companies or with external companies possessing high resources and capabilities. Such alliances are considered an effective strategic alternative to ensure the survival, continuity, and growth of these companies.